PD-1IR2 promotes tumor evasion via deregulating CD8+ T cell function - Xiaodong Wang; Shan Gao; Xiaofeng Zhu; Hongbo Hu; Fang Guo; Shuwen Cheng; Chang Huang; Haojing Zang; Tongfeng Liu; Liqiang Duan; Xujie Zhao; Xuetong Wang; et al. (Journal for ImmunoTherapy of Cancer)
Background The programmed cell death 1 (PD-1) is an immune checkpoint that mediates immune evasion of tumors. Alternative splicing (AS) such as intron retention (IR) plays a crucial role in the immune-related gene processing and its function. However, it is not clear whether PDCD1 encoding PD-1 exists as an IR splicing isoform and what underlying function of such isoform plays in tumor evasion.Methods An AS isoform of human PDCD1, characterized by the second IR and named PD-1IR2, was identified by reverse transcription-PCR (RT-PCR) and Sanger sequencing. The expression profile of PD1IR2 was assessed by quantitative RT-PCR and flow cytometry, while its function was evaluated through immune cell proliferation, cytokine interleukin 2 secretion, and tumor cell killing assays. PDCD1IR2 CKI mice which specifically conditional knock-in PDCD1IR2 in T cells and humanized peripheral blood mononuclear cells (PBMC)-NOG (NOD.Cg-PrkdcscidIL2rgtm1Sug/JicCrl) mice were utilized to further confirm the physiological function of PD-1IR2 in vivo.Results PD-1IR2 is expressed in a variety of human leukemia cell lines and tumor-infiltrating lymphocytes. PD-1IR2 expression is induced on T cell activation and regulated by the RNA-binding protein hnRNPLL. PD-1IR2 negatively regulates the immune function of CD8+ T cells, indicated by inhibiting T cell proliferation, cytokine production, and tumor cell killing in vitro. PD-1IR2+ CD8+ T cells show impaired antitumor function, which consequently promote tumor evasion in a conditional knock-in mouse model and a PBMC-engrafted humanized NOG mouse model. PD-1IR2 mice exhibit resistance to anti-PD-L1 therapy compared with wild-type mice.Conclusions PD-1IR2 is a potential immune checkpoint that may mediate potential resistance to immune checkpoint therapy.